Model-Based Analysis of Context-Specific Cognitive Control - King, Joseph A.; Donkin, Christopher; Korb, Franziska M.; Egner, Tobias (Frontiers in Psychology, 2012)
Interference resolution is improved for stimuli presented in contexts (e.g. locations) associated with frequent conflict. This phenomenon, the “context-specific proportion congruent” (CSPC) effect, has challenged the traditional juxtaposition of “automatic” and “controlled” processing because it suggests that contextual cues can prime top-down control settings in a bottom-up manner. We recently obtained support for this “priming of control” hypothesis with fMRI by showing that CSPC effects are mediated by contextually-cued adjustments in processing selectivity. However, an equally plausible explanation is that CSPC effects reflect adjustments in response caution triggered by expectancy violations (i.e. prediction errors) when encountering rare events as compared to common ones (e.g. high-conflict incongruent trials in a task context associated with infrequent conflict). Here, we applied a quantitative model of choice, the linear ballistic accumulator (LBA), to distil the reaction time and accuracy data from four independent samples that performed a modified flanker task into latent variables representing the psychological processes underlying task-related decision making. We contrasted models which differentially accounted for CSPC effects as arising either from contextually-cued shifts in the rate of sensory evidence accumulation (“drift” models) or in the amount of evidence required to reach a decision (“threshold” models). For the majority of the participants, the LBA ascribed CSPC effects to increases in response threshold for contextually-infrequent trial types (e.g. low-conflict congruent trials in the frequent conflict context), suggesting that the phenomenon may reflect more a prediction error-triggered shift in decision criterion rather than enhanced sensory evidence accumulation under conditions of frequent conflict.